2011
DOI: 10.1177/070674371105600404
|View full text |Cite
|
Sign up to set email alerts
|

Are Canadians Providing Advance Directives about Health Care and Research Participation in the Event of Decisional Incapacity?

Abstract: Advance planning has increased over the last 2 decades in Canada. Nonetheless, further efforts are needed to encourage Canadians to voice their health care and research preferences in the event of incapacity. Physicians are well situated to promote advance planning to Canadians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
19
0
2
Order By: Relevance
“…While information about this topic is scant and relatively outdated, studies examining these issues consistently show low prevalence rates ( 18 , 21 , 27 , 28 ), and three main correlates of ARD: previous research experience, health care directives and the level of risk or side effects involved in the research protocol. Finally, it should be noted that there is no knowledge at all regarding these issues either in Germany or in Israel.…”
Section: Introductionmentioning
confidence: 99%
“…While information about this topic is scant and relatively outdated, studies examining these issues consistently show low prevalence rates ( 18 , 21 , 27 , 28 ), and three main correlates of ARD: previous research experience, health care directives and the level of risk or side effects involved in the research protocol. Finally, it should be noted that there is no knowledge at all regarding these issues either in Germany or in Israel.…”
Section: Introductionmentioning
confidence: 99%
“…Despite widespread professional and public endorsement of ADs for health care, still too few people actually execute them or even discuss future treatment wishes with loved ones or healthcare practitioners [2,18,22,24,25]. The most common reasons include trusting family members to make the right decision when the time comes, the tendency to defer end-of-life planning until facing a life-threatening illness, a lack of knowledge about ADs, and limited access to needed forms [11].…”
Section: Introductionmentioning
confidence: 99%
“…The most common reasons include trusting family members to make the right decision when the time comes, the tendency to defer end-of-life planning until facing a life-threatening illness, a lack of knowledge about ADs, and limited access to needed forms [11]. According to our own survey [25], even fewer have voiced their wishes in relation to research involvement. Interestingly, survey participants who had done so were more likely to have conveyed their preferences for care.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, many people do not give advance directive plans about their participation in research after their decision-making capacity is lost [48] Aaronson and Burman [44] Hall et al [1] Assess the quality and completeness of the charts that will be used for data collection *Note: Authors of three studies reported that, the quality of the charts was excellent [28,29,34]. However, the quality of charts should not always be assumed…”
Section: Keay Et Al [40]mentioning
confidence: 99%